Criminal Liability for Companies That Register Part of the BPJS Employment Program - Ayu Eka Putri Lawolo; Sanco Simanullang; Habieb Pahlevi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The high number of Partial Listed Companies (PDS) manipulating the number of employees, wages, and programs to avoid paying high social security contributions highlights companies' non-compliance with BPJS Ketenagakerjaan. Only 2.93% of workers in Indonesia were registered with BPJS Ketenagakerjaan in 2021, indicating low compliance among companies in participating in health and occupational safety assurance programs. The aim of this study is to describe the criminal risks faced by PDS in the BPJS Ketenagakerjaan program to highlight the sanctions against non-compliance in implementing social security programs. This research uses a qualitative approach with literature studies and normative juridical methods based on Law No. 14 of 2011 on the Social Security Administrative Body (BPJS). The results of the study show that PDS is an unlawful act due to non-compliance with the obligation to pay BPJS contributions. The types of PDS commonly carried out by companies include PDS of employees, PDS of wages, and PDS of programs. Criminal liability for PDS includes administrative sanctions, such as two written warnings within a maximum period of 30 days, administrative fines of 0.1% of total contributions, and restrictions on accessing certain public services (TMP2T), such as difficulties in obtaining business permits, participating in project tenders, hiring foreign workers, and obtaining building permits (IMB).